2003
DOI: 10.4490/algae.2003.18.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Sewage and Wastewater Plant Effluent on the Algal Growth Potential in the Nakdong River Basin

Abstract: Effect of the effluent of the sewage and wastewater plants on the algal growth was investigated from the 19 plants located in the Nakdong river basin. Most of the samples showed high values of the algal growth potential (AGP) when they were mixed with natural river water at 20% of final concentration. At 20% of the mixing ratio, the mixed effluents of sewage and wastewater showed 3.5 and 1.8 times higher AGP than those of the natural river water. The higher AGP values are attributable to the high contents of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Irrespective of the treatment processes, the AGP values decreased as the volume of dilution increased. These results were consistent with previous studies that explained a correlation between the increase in dilution ratio and the decrease in AGP values (Seo et al, 2003;Shin et al, 2000). Although the growth rate and biomass accumulation of M. aeruginosa are considered to be complex functions related to nutrient availability and settings of aquatic ecosystems (e.g., water temperature, sunlight, water velocity, turbidity, salinity, etc.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Irrespective of the treatment processes, the AGP values decreased as the volume of dilution increased. These results were consistent with previous studies that explained a correlation between the increase in dilution ratio and the decrease in AGP values (Seo et al, 2003;Shin et al, 2000). Although the growth rate and biomass accumulation of M. aeruginosa are considered to be complex functions related to nutrient availability and settings of aquatic ecosystems (e.g., water temperature, sunlight, water velocity, turbidity, salinity, etc.…”
Section: Resultssupporting
confidence: 94%
“…Although there are multiple limiting nutrients (e.g., nitrogen, phosphorus, iron, etc.) in natural aquatic systems (Biggs, 2000;Donald et al, 2013;Parrish, 2014;Xu et al, 2010), SRP-limited growth of M. aeruginosa using reclaimed water from various WRRFs was proposed (Paerl et al, 2011;Seo et al, 2003). Thus, the SRPlimited growth of M. aeruginosa was evaluated in this study using the Monod's equation (Monod, 1949), as shown in eq 2,…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations